PERLINDUNGAN KONSUMEN TERHADAP BARANG YANG TIDAK SESUAI DENGAN YANG DIPERJANJIKAN OLEH PELAKU USAHA MENURUT MENURUT UNDANG-UNDANG NOMOR 8 TAHUN 1999 TENTANG PERLINDUNGAN KONSUMEN - Markus Hamonangan; Jeane Neltje Saly (Fakultas Hukum Universitas Tarumanagara, 2021)
Consumer protection is regulated in Law No. 8 of 1999 on Consumer Protection. Article 4 explains that one of the rights of consumers is the right to comfort, security, and safety in consuming goods and / or services. Consumer protection efforts to ensure legal certainty to provide consumer protection so that consumers get their rights as consumers with consumer protection involving business actors aim to maintain the condition of the trading world so that conducive not to be full of violations and aim to keep business actors doing, as an effort to protect consumers, but has not been achieved optimally can be seen in the case of goods that are not in accordance with consumer orders, because business people send goods that are not in accordance with what is promised to consumers. The application of legal protection to consumers is not in accordance with the laws and regulations contained in Consumer Protection Law No. 8 of 1999, causing problems. The type of research used by the author is a legal research method for academic purposes This research examines various documents related to research. Authors use normative legal research methods using statute approach and case approach.